To determine the effectiveness of physical therapy management among the toe walking children's in Karachi Pakistan: An observational study - Vikash Chughani; Sonum Sachdev; Shobha Lekhraj; Aadil Ameer Ali (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2021)
Objective: To evaluate the effectiveness of Physical Therapy Management among the toe walking children's in Karachi Pakistan.  Methodology: A cross sectional survey was conducted from June to October 2018 in Department of physiotherapy, Liaquat National medical college and hospital, Karachi, Pakistan. A self-fabricated questionnaire was used in 36 Toe walking children's. The questionnaire consists of demographics (age and gender), evaluation of pain through visual analogue scale, range of motion through goniometer and cadence was measured .The statistical package for social sciences (SPSS) version 23 was used to interpret the data. Result: The majority (n=24, 66.6%) were belongs to age group of 8 to 12 years and (n=25, 69.4%) were male. Mostly (n=25, 69.4%) were clinically diagnosed cases of cerebral palsy. After checking the involvement it was found that (n=21, 58.3%) were suffering from bilateral toe walking and (n=22, 61.1%) were affected from the day of their birth. Conclusion: The study finalized that the Physical Therapy is effective in decreasing the pain, increasing the range of motion and improving the number of steps among the toe walking children's.